Cases report: Mosaic structural variants of the EXT1 gene in previously genetically unconfirmed multiple osteochondromas - Borovikov, Artem; Marakhonov, Andrey; Murtazina, Aysylu; Davydenko, Kseniya; Filatova, Alexandra; Galeeva, Nailya; Kadnikova, Varvara; Ogorodova, Natalya; Gorodilova, Daria; Kanivets, Ilya; Pyankov, Denis; Zherdev, Konstantin; et al. (Frontiers in Genetics, 2024)
Multiple osteochondromas (MO) is a rare autosomal dominant skeletal disorder characterized by the development of multiple benign tumors known as osteochondromas. The condition is predominantly caused by loss-of-function variants in the EXT1 or EXT2 genes, facilitating relatively precise clinical diagnosis through established diagnostic criteria. Despite this, a notable percentage of MO cases (10%–20%) remains unresolved after sequencing coding regions and copy number analysis of both genes. In our study, we identified mosaic structural variants in two patients who initially yielded negative results on standard genetic analysis for MO. Specifically, mosaic deletions affecting exons 8–11 and exons 2–11 in the EXT1 gene were detected. RNA analysis was performed in one case, while both cases underwent genome sequencing. To date, only six mosaic copy number variations have been reported in association with MO, representing a minority among known variants in both genes. Our report provides a detailed analysis of these findings, highlighting the significance of advanced genetic testing techniques in detecting mosaic variants in the EXT1/2 genes.